Praktik Kesehatan Reproduksi pada Remaja Pasca Penyuluhan - Wiryaningsih, Gusti Ayu Gita; Lerik, M. Dinah Charlota; Lada, Christina Olly (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study was to analyze the influence of adolescent knowledge, the role of teachers, the role of parents, the role of peers and access to information media on reproductive health practices in post-counseling adolescents. This research method used cross sectional, sample was 287 people, using stratified sampling technique. The results of the study showed the factors that influence reproductive health practices are knowledge (p = 0.000), the role of teachers (p = 0.000), the role of parents (p = 0.006), the role of peers (p = 0.022) while access to information media (p = 0.877) is not a factor affecting reproductive health practices. The conclusion was knowledge, the role of teachers, the role of parents, and the role of peers factors influence adolescents reproductive health practice, while access to information media is not a factor that influence adolescents reproductive health practice in post-counseling adolescent. Keywords: Health Reproduction, Adolescent, Counseling